To find the height \( h \) of the square pyramid, we can utilize the right triangle formed by the height, the slant height, and half the base length.
First, let's denote the following:
- The lateral edge length \( e = 25 \) inches
- The slant height \( s = 24 \) inches
- The height \( h \) (which we need to find)
- The half base edge length \( \frac{b}{2} \)
Since it's a square pyramid, we can use the Pythagorean theorem on the triangle formed by the height \( h \), half the base length \( \frac{b}{2} \), and the slant height \( s \):
\[ s^2 = h^2 + \left(\frac{b}{2}\right)^2 \]
Unfortunately, we need to find \( b \) (the length of the base edge) before we can proceed. The relationship between the lateral edge \( e \), height \( h \), and half the base length \( \frac{b}{2} \) can also be expressed using another right triangle formed:
\[ e^2 = h^2 + \left(\frac{b}{2}\right)^2 \]
Now, we have two equations:
- \( s^2 = h^2 + \left(\frac{b}{2}\right)^2 \)
- \( e^2 = h^2 + \left(\frac{b}{2}\right)^2 \)
We can set these equal to each other and substitute \( s \) and \( e \):
- \( 24^2 = h^2 + \left(\frac{b}{2}\right)^2 \)
- \( 25^2 = h^2 + \left(\frac{b}{2}\right)^2 \)
Calculating the squares: \[ 576 = h^2 + \left(\frac{b}{2}\right)^2 \] \[ 625 = h^2 + \left(\frac{b}{2}\right)^2 \]
Setting both equations equal to each other, since they equal \( h^2 + \left(\frac{b}{2}\right)^2 \): \[ 576 = 625 \] This doesn’t help as there’s no \( b \) directly relating to \( h \) and \( s \) or \( e \) yet.
Instead, we'll simply begin by transforming the two equations to isolate \( h \): From \( e^2 = h^2 + \left(\frac{b}{2}\right)^2 \) and \( s^2 = h^2 + \left(\frac{b}{2}\right)^2 \), we can find that: \[ e^2 - s^2 = (h^2 + \left(\frac{b}{2}\right)^2) - (h^2 + \left(\frac{b}{2}\right)^2) \] Rearranging gives us: \[ 625 - 576 = 49 = \left(\frac{b}{2}\right)^2 - (y^2) \]
This does not help us directly find \( h \) without \( b \).
Thus we can break back from previously expressing \( \frac{b}{2} \) from both triangles' earlier approaches. Knowing: \[ \left(\frac{b}{2}\right)^2 = e^2 - h^2 = 625 - h^2 \]
And \( \left(\frac{b}{2}\right)^2 = s^2 - h^2 = 576 - h^2\)
Setting these equal to each other gives: \[ 625 - h^2 = 576 - h^2 \]
The inconsistency leads us back to the equation, from the height: Using \( s = 24 \text{ and } e = 25 \) leads us to how; \( e^2 = h^2 + 576, h^2 = 25^2 - 12^2 \): \[ h^2 = 625 - 576 = 49; \ h = 7 \]
So the height \( h \approx 7 \text{ inches.} \) Thus: Final Answer: \( h = 7 , \text{inches} \). (Rounded to nearest whole number.)